Pembelajaran Tari Selayang Pandang Di Panti Sosial Bina Netra “Tuah Sakato” Padang - Risna Rilantia; Fuji Astuti; Afifah Asriati (FBS Universitas Negeri Padang, 2019)
This study aimed to describe the process and “Selayang Pandang” Dance art learning for blind students at PSBN TUAH SAKATO Padang. This type of research used a qualitative descriptive approach. The types of data in this study were primary data and secondary data. The techniques of data collection were by observing 6 people, interviews with instructors and documentation. The main instrument in this study was the researchers themselves and assisted with supporting instruments such as notebooks and digital cameras / mobile phone cameras. Techniques of data analysis were carried out with the following steps: observing, describing data, and concluding the results of the discussion. The results of the “Selayang Pandang” Dance art learning was well shown by the results of evaluations of 6 children who were 4 of them have achieved good category scores, 1 child reaches a very good category, and only 1 child with enough category. However, the process of learning dance art at PSBN TUAH SAKATO is successful, because even though children with disabilities can dance as normal children.